Displacement-Based Seismic Design Approach for Prestressed Precast Concrete Shear Walls and its Application. Issue 10 (26th November 2018) - Yang, Boya; Lu, Xilin
ABSTRACT: Prestressed precast concrete shear wall (PPCW) is a new kind of shear wall utilizing a combination of unbonded post-tensioning steel and mild steel for flexural resistance across horizontal joints. A simple procedure of direct displacement-based design approach for PPCW based on concept of inelastic design spectra is proposed. Section design is then carried out according to base overturning moment. A detailed design example demonstrating a step-by-step application of the design procedure is also provided. Nonlinear time-history analysis verified that this approach is applicable to control the target displacement to the performance acceptable limit.